Survey of the Practice of Spinal Cord Stimulators and Intrathecal Analgesic Delivery Implants for Management of Pain in Canada - Philip WH Peng; Ingrid Fedoroff; Line Jacques; Krishna Kumar (Pain Research and Management)
BACKGROUND: In 2006, the Canadian Neuromodulation Society was formed. The present survey characterizes the practice of spinal cord stimulator (SCS) and intrathecal analgesic delivery pump (IADP) implantation for pain management in different centres across Canada.